2017
DOI: 10.1007/s10897-017-0171-y
|View full text |Cite
|
Sign up to set email alerts
|

“Yeah that Made a Big Difference!”: The Importance of the Relationship between Health Professionals and Fathers Who Have a Child with Down Syndrome

Abstract: Evidence suggests that medical services do not reflect the increased involvement of fathers in childcare, a discrepancy that can often lead to feelings of exclusion and inequality. Fathers who have a child with Down syndrome may encounter many different health professionals during their child's life, therefore it is important to consider this relationship, and investigate the factors that influence their experiences. This is particularly important because the limited research focusing on fathers suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
2
0
4
Order By: Relevance
“…It has been identified that some parents report managing their chronic uncertainty by reframing it more positively, as a source of hope for the future (Rafferty et al, 2019) and that parents might even wish to avoid information that threatens this hope (Hinton & Kirk, 2017). This finding is reflected in other studies that warn about the potential unsettling effects of providing overly negative information (Docherty & Dimond, 2018; Gibson, 2016) or information that parents are not ready for (Reeder & Morris, 2018). Interestingly, the idea of uncertainty as a source of hope is at odds with Penrod's conceptualization, which implies that such unresolved uncertainty does not allow space for hope (Morse & Penrod, 1999).…”
Section: Introductionmentioning
confidence: 74%
“…It has been identified that some parents report managing their chronic uncertainty by reframing it more positively, as a source of hope for the future (Rafferty et al, 2019) and that parents might even wish to avoid information that threatens this hope (Hinton & Kirk, 2017). This finding is reflected in other studies that warn about the potential unsettling effects of providing overly negative information (Docherty & Dimond, 2018; Gibson, 2016) or information that parents are not ready for (Reeder & Morris, 2018). Interestingly, the idea of uncertainty as a source of hope is at odds with Penrod's conceptualization, which implies that such unresolved uncertainty does not allow space for hope (Morse & Penrod, 1999).…”
Section: Introductionmentioning
confidence: 74%
“…Актуализируются потребности отцов в нахождении ресурсов, позволяющих им справляться с трудной ситуацией и поддерживать своих детей с особенностями развития, в частности детей с синдромом Дауна [DeFalco et al, 2008;Docherty, Dimond, 2018]. Несмотря на повышение отцовского участия в уходе за детьми в последнее время, поддержка отцов чаще рассматривается как «вторичная», и пока мало известно о ее характере, разнообразии и воздействии на благополучие детей-инвалидов и семьи в целом, предпринимаются лишь отдельные попытки типологизации участия отцов и описания более полной картины внутрисемейного взаимодействия [West, Honey, 2016].…”
Section: теоретические основания исследованийunclassified
“…Несмотря на то, что отцы сообщают о высоком уровне уважения к медицинскому персоналу и благодарности за помощь, распространены сообщения отцов о возникающих у них негативных чувствах -изоляции, недооцененности, беспомощности, неравенства, отчуждения, вызванных пренебрежительным отношением к их мнению, различиями в обращении медперсонала с мужчинами по сравнению с их женами, безразличным отношением к их бытовым потребностям при нахождении в больнице. Все это заставляет отцов чувствовать, что медицинский персонал не считает их равноценными или важными родителями [Docherty, Dimond, 2018].…”
Section: культурные барьерыunclassified
See 2 more Smart Citations